Basketball talent identification: a systematic review and meta-analysis of the anthropometric, physiological and physical performance factors - Han, Miaoyu; Gómez-Ruano, Miguel-Angel; Calvo, Alberto Lorenzo; Calvo, Jorge Lorenzo (Frontiers in Sports and Active Living, 2023)
1) Background: The purpose of this study was to do a systematic review and meta-analysis about the anthropometric, physiological, and physical performance that discriminate the physical talent in basketball; (2) Methods: The search was conducted using the most relevant databases as Web of Science, PubMed, SPORTDiscus and Scopus, according to the PRISMA (2020) guideline. Keywords as basketball", "talented identification", "anthropometric", "physiology" and "physical performance" were used for the search, in English and following the 'PICOS' question model. Eighteen articles' overall methodological quality was assessed using the Critical Review Forms; (3) Results: The study found in basketball, height, body mass, Yo-Yo test, T-test, 20 m sprint, and jump performance had statistical significance between elite and non-elite groups, including different positions and levels. (4) Conclusions: The reviewed literature highlighted a complicated relationship between anthropometric, physiological, and physical performance. Based on the results of the study, it's possible that height, body mass, agility, speed, endurance capacity, and lower lamb power could affect the early development of basketball.